A life-cycle analysis of deep enhanced geothermal systems – The case studies of Reykjanes, Iceland and Vendenheim, France. (November 2021) - Sigurjónsson, Hafþór Ægir; Cook, David; Davíðsdóttir, Brynhildur; Bogason, Sigurður G.
Abstract: The climate impacts of deep enhanced geothermal systems (EGS) have been understudied in the academic literature. Using life-cycle analysis (LCA) conducted in accordance with ISO 14040 and ISO 14044 standards, this paper explores the climate change impacts of two deep EGS. The first study was in Reykjanes, Iceland, where a single well, IDDP-2/DEEPEGS, was drilled to a depth of 4.6 km for the purposes of additional electricity production from an existing power plant. The second study involved two wells with side-tracks (depth > 5000 m), drilled to serve a new heat and power co-generation plant located on an old oil field site in Vendenheim, France. Climate change impacts for the sites were estimated in the range 1.6–17.4 gCO2e/kWh and 6.9–13.9 gCO2e/kWh for Reykjanes and Vendenheim, respectively. Although the EGS projects are very different, both outcomes are low when compared to non-renewable alternatives and akin to best-in-class renewable alternatives. The main impact at the Reykjanes demonstration site were the greenhouse gas emissions released from the borehole, an effect that could be avoided by carbon capture and storage/mineralisation/utilisation. In the case of Vendenheim, further reductions in emissions could be achieved via more extensive adoption of circular economy principles in design and procurement. Highlights: First two life-cycle assessments of deep enhanced geothermal systems (EGS). Climate change impacts for Reykjanes estimated in the range 1.6–17.4 gCO2e/kWh. Climate change impacts for Vendenheim estimated in the range 6.9–13.9 gCO2e/kWh. Emissions reductions at Reykjanes achievable through carbon capture and storage. Circular economy design/procurement principles could reduce emissions at Vendenheim.